Ligand dependent magnetism of the Jeff = 3/2 Mott insulator Cs2MX6 (M = Ta, Nb, X = Br, Cl). (18th January 2021) - Ishikawa, Hajime; Yajima, Takeshi; Matsuo, Akira; Kindo, Koichi
Abstract: Magnetic and structural properties of double perovskite type bromides Cs2 M Br6 ( M = Ta, Nb), where Ta 4+ (5 d 1 ) and Nb 4+ (4 d 1 ) ions form the face centered cubic lattice, are investigated and compared with chlorides Cs2 M Cl6 . Cs2 TaBr6 exhibits the effective magnetic moment of 0.24 μ B, which is much smaller than the spin only value of a d 1 ion, 1.73 μ B, and comparable to 0.25 μ B in Cs2 TaCl6 . On the other hand, the effective magnetic moment of Cs2 NbBr6 is 0.7 μ B and is substantially smaller than 1.0 μ B in Cs2 NbCl6 . On cooling, successive structural and magnetic phase transitions accompanying the release of electronic entropy approximately R ln 4 in total as expected for the J eff = 3/2 state are observed. The type of the ligand changes the temperature dependence of magnetic susceptibility at low temperature as well as its magnitude. The role of the ligands on the magnetism of J eff = 3/2 Mott insulators are discussed in the light of metal–ligand hybridization and the electron–lattice coupling.